Analisis Isi Kurikulum Pendidikan Agama Islam di Madrasah Berdasarkan Standar Nasional Pendidikan - Niza Putri Nurfajrin; Muhammad Zuhdi; Bobi Erno Rusadi (Advances In Education Journal, 2025)
The curriculum serves as a primary component in the education system, determining the direction, content, and strategies for implementing learning. In the context of Islamic Religious Education (PAI) in madrasahs, the curriculum functions not only as an academic guide but also as a means of shaping Islamic values and the character of students. This research aims to analyze the content of the PAI curriculum in madrasahs in relation to its relevance to the needs of students in the modern era, as well as its alignment with the goals of Islamic education. The method employed is qualitative research using a library research approach, through analysis of various literature sources such as books, scientific journals, government regulations, and previous research findings. The research findings indicate that the PAI curriculum in madrasahs has a comprehensive structure encompassing four main subjects: Al-Qur’an Hadith, Akidah Akhlak, Fiqh, and History of Islamic Culture, with greater time allocation and depth of material compared to general schools. However, gaps still exist between the ideal curriculum and its field implementation, particularly in teachers' understanding of the curriculum content and the application of contextual learning. Therefore, strengthening teacher capacity, aligning central and regional policies, and innovating value-based Islamic learning relevant to contemporary challenges are necessary.